A retrofit decision support approach for improving energy efficiency and indoor environmental quality in buildings - Asadi, Ehsan (2013)
Tese de doutoramento em Sistemas Sustentáveis de Energia, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra